2008
DOI: 10.1183/09031936.00122508
|View full text |Cite
|
Sign up to set email alerts
|

Assessing response to treatment of exacerbations of bronchiectasis in adults

Abstract: The present study aimed to assess the effect of intravenous antibiotic therapy on clinical and laboratory end-points in exacerbations of noncystic fibrosis bronchiectasis and to determine whether the outcomes were influenced by the pathogenic organism isolated.A prospective cohort study was conducted from November 2006 to March 2008 of exacerbations requiring intravenous antibiotics. End-points included 24-h sputum volume, forced expiratory volume in one second (FEV1), forced vital capacity (FVC), incremental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 24 publications
3
83
1
4
Order By: Relevance
“…The increased systemic inflammation during exacerbations could be abrogated by antibiotics. In the study by Murray et al, 11 24-h sputum volume, C-reactive protein, and SGRQ scores were responsive to therapeutic outcomes, but were unrelated to bacterial clearance. Courtney et al 12 reported a notable decline in serum C-reactive protein, sputum inflammatory cell counts, and biomarkers (TNF-␣, CXCL8, and neutrophil elastase), but not spirometry or SGRQ scores, at day 14 following antibiotic therapy.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The increased systemic inflammation during exacerbations could be abrogated by antibiotics. In the study by Murray et al, 11 24-h sputum volume, C-reactive protein, and SGRQ scores were responsive to therapeutic outcomes, but were unrelated to bacterial clearance. Courtney et al 12 reported a notable decline in serum C-reactive protein, sputum inflammatory cell counts, and biomarkers (TNF-␣, CXCL8, and neutrophil elastase), but not spirometry or SGRQ scores, at day 14 following antibiotic therapy.…”
Section: Discussionmentioning
confidence: 90%
“…C-reactive protein has been reported to be a useful parameter in reflecting the efficacy of antibiotic therapy following bronchiectasis exacerbations; therefore, we calculated the sample size according to the pre-and posttreatment C-reactive protein based on the study of Murray et al 11 It has been shown that antibiotics lead to a significant reduction in C-reactive protein levels (6.7 Ϯ 7.1 vs 0.7 Ϯ 1.1 mg/dL). By assuming the levels of ␣ and ␤ to be 0.05 and 0.10 (2-sided tests), respectively, we estimated that 15 subjects…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, several studies concluded that exacerbations in subjects with bronchiectasis can adversely affect HRQOL, and treatment of exacerbations might lead to improvement in quality of life. [22][23][24] It is clear that this issue needs more study. People live with chronic diseases that can adversely affect their HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial clearance, 24-hour sputum volume, C-reactive protein and the St George's Respiratory Questionnaire (an HRQL questionnaire) are useful markers of treatment response, although the latter questionnaire is predominantly a research tool. 31,32 …”
Section: Assessing Responsementioning
confidence: 99%